Mucosal immunity, respiratory illness, and competitive performance in elite swimmers - Pyne, D. B.; McDonald, W. A.; Gleeson, M.; Flanagan, A.; Clancy, R. L.; Fricker, P. A. (Medicine & Science in Sports & Exercise, 2001)
Purpose: Exercise and training are known to elicit changes in mucosal humoral immunity, but whether these alterations have any impact on competitive performance remains unclear. This investigation examined relationships between salivary immunoglobulin (Ig) concentration, the incidence of respiratory tract illness (RTI), and competitive performance in elite swimmers. Methods: Forty-one members of the Australian Swimming Team (21 males and 20 females) aged 15-27 yr were monitored during preparations for the 1998 Commonwealth Games. Twenty-five coaches and staff (19 males and 6 females) aged 32-65 yr, serving as "environmental controls," were also monitored. Salivary IgA, IgM, and IgG and albumin concentration (mg.L-1) were measured in both groups in May 1998 and again in August 1998, 17 d before competition. Subjects were categorized as "ill" (at least one RTI) or "healthy". Results: There were no significant changes in salivary IgA, IgM, or IgG concentration in the swimmers between May and August, nor were there any differences between healthy (N = 23) and ill (N = 18) swimmers. There was a significant positive relationship between IgM and performance in the male swimmers (r = 0.85, P < 0.001) but not for any other parameter. There was no significant difference in performance between ill and healthy swimmers (P = 0.11). Gold medal winners (N = 9) had higher IgM levels than other swimmers (N = 32) in May (P = 0.02) and higher IgG in August (P = 0.02). Conclusion: These data indicate that a season of training by elite swimmers did not alter salivary immunoglobulin concentrations, and the presence of RTI had no significant impact on competitive performance.